2021
DOI: 10.7554/elife.67023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19-related disruptions to measles, meningococcal A, and yellow fever vaccination in 10 countries

Abstract: Background: Childhood immunisation services have been disrupted by COVID-19. WHO recommends considering outbreak risk using epidemiological criteria when deciding whether to conduct preventive vaccination campaigns during the pandemic. Methods: We used 2-3 models per infection to estimate the health impact of 50% reduced routine vaccination coverage and delaying campaign vaccination for measles, meningococcal A and yellow fever vaccination in 3-6 high burden countries per infection. Results: Reduced routine co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 33 publications
1
55
0
4
Order By: Relevance
“…Consequently, the focus in children in low-and middle-income countries (LMICs) including Bangladesh has typically been addressing key concerns including poor vaccination rates as a result of lockdown and other activities [51][52][53] . In Bangladesh, this includes organising immunisation outreach services, tracking children who had missed their vaccinations as well as increasing home visits by health workers 53,54 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the focus in children in low-and middle-income countries (LMICs) including Bangladesh has typically been addressing key concerns including poor vaccination rates as a result of lockdown and other activities [51][52][53] . In Bangladesh, this includes organising immunisation outreach services, tracking children who had missed their vaccinations as well as increasing home visits by health workers 53,54 .…”
Section: Introductionmentioning
confidence: 99%
“…They found the benefits outweighed the costs with 84 (95% uncertainty interval 14-267) child deaths averted by sustained childhood immunisation per 1 excess COVID-19 death even with the risks associated with vaccination clinic visits. The VIMC Working Group on COVID-19 Impact on VPDs analysed the effect of COVID-19 disruption on measles, MenA and YF through modelling scenarios of routine immunisation service disruptions and mass vaccination campaign suspensions in a subset of countries ( Gaythorpe et al, 2021b ). They found that the nature of the disease affects the impact of vaccination activity disruption; for example, YF and measles affect younger age groups and are prone to outbreaks, thus short-term disruption will likely increase burden.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the effect of COVID-19 is not the focus of the current study, we acknowledge the huge influence the global pandemic has had and will have for years to come. Preliminary work has begun on quantifying the effect of disruption on vaccination activities and on assessing the benefit of continuing routine infant immunisation in times of COVID-19 ( Abbas et al, 2020a ; Gaythorpe et al, 2021b ). There is also evidence that the rise in non-pharmaceutical interventions (NPIs, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Routine childhood vaccines should not be interrupted, since the risk of children dying as a result of not receiving these vaccines far outweighs the risk of dying from COVID-19 as a result of attending a vaccine clinic [10]. For vaccine campaigns, the risk of outbreaks as a result of postponing campaigns varies across settings and pathogens [11]. For some vaccines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previous modelling studies have demonstrated that the benefits of continuing routine immunisation likely outweigh the excess risk from COVID-19 but did not examine campaign delivery [10]. A recent study has examined the risks of vaccine-preventable disease outbreaks (measles, meningococcal A, and yellow fever) associated with delaying immunisation campaigns, which varied across countries [11]. Another study assessed the risk of measles outbreaks in Kenya and found that although COVID-19 interventions also temporarily reduced the risk of an outbreak from measles immunity gaps, this risk rises rapidly once these restrictions are lifted highlighting the need to implement catch-up campaigns [12].…”
Section: Introductionmentioning
confidence: 99%